Cardioprotection leads to novel changes in the mitochondrial proteome - Wong, Renee (American Physiological Society, 2010)
It is proposed that ischemic preconditioning (PC) initiates signaling that converges on mitochondria and results in cardioprotection. The outcome of this signaling on mitochondrial enzyme complexes is yet to be understood. We therefore used proteomic methods to test the hypothesis that PC and pharmacological preconditioning similarly alter mitochondrial signaling complexes. Langendorff-perfused murine hearts were treated with the specific GSK-3 inhibitor AR-A014418 (GSK Inhib VIII) for 10 min or subjected to four cycles of 5-min ischemia-reperfusion (PC) before 20-min global ischemia and 120-min reperfusion. PC and GSK Inhib VIII both improved recovery of postischemic left ventricular developed pressure, decreased infarct size, and reduced lactate production during ischemia compared with their time-matched controls. We used proteomics to examine mitochondrial protein levels/posttranslational modifications that were common between PC and GSK Inhib VIII. Levels of cytochrome-c oxidase subunits Va and VIb, ATP synthase-coupling factor 6, and cytochrome b-c1 complex subunit 6 were increased while cytochrome c was decreased with PC and GSK Inhib VIII. Furthermore, the amount of cytochrome-c oxidase subunit VIb was found to be increased in PC and GSK Inhib VIII mitochondrial supercomplexes, which are comprised of complexes I, III, and IV. This result would suggest that changes in complex subunits associated with cardioprotection may affect supercomplex composition. Thus the ability of PC and GSK inhibition to alter the expression levels of electron transport complexes will have important implications for mitochondrial function.